Carcinoma cuniculatum of the esophagus-diagnostic and treatment dilemma - Matheus Falasa; Alexander Ayzengart; Michael Walters; Xiuli Liu; Olusola Oduntan (Archives of Clinical Gastroenterology - Peertechz Publications, 2020)
Carcinoma cuniculatum is a rare variant of well-differentiated squamous cell carcinoma of the esophagus, with fewer than twenty cases reported in the literature [1]. Diagnosis is often delayed due to failure of endoscopic biopsies to yield a definitive tissue diagnosis. We present the case of a patient with carcinoma cuniculatum of the esophagus who was misdiagnosed as achalasia, and consequently did not undergo surgical resection of the malignancy for nine months.